Caspase-8 activation in neutrophils facilitates autoimmune kidney vasculitis through regulating CD4+ effector memory T cells - Hu, Jian; Huang, Zhen; Yu, Min; Zhang, Pei; Xia, Zhengkun; Gao, Chunlin (Frontiers in Immunology, 2022)
Anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitides (AAVs) are closely associated with neutrophil recruitment and activation, but the impact of the neutrophil apoptosis process in autoimmune disease has been rarely explained. Here, by integrating and analyzing single-cell transcriptome datasets, we found that the caspase-8-associated pathway in neutrophils was highly activated in the kidney rather than in the blood. To verify the function of caspase-8 in neutrophils on AAVs progression, we constructed neutrophil-specific caspase-8 knockout mice combined with an AAVs model induced by human ANCA from AAVs patients, a rapid and powerful model developed in this study. Our results show that caspase-8 activation of neutrophils up-regulates the expression of several inflammatory and immunoregulatory factors, especially IL23A, regulating the activation and differentiation of tissue-resident CD4+ effector memory T cells. This study reveals that the activation of caspase-8 in neutrophils can worsen glomerulonephritis of AAVs by regulating inflammation and immunity.